2012
DOI: 10.1097/wox.0b013e3182784ee0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Probiotics in Pediatric Allergy (cuppa): A World Allergy Organization Position Paper

Abstract: BackgroundProbiotic administration has been proposed for the prevention and treatment of specific allergic manifestations such as eczema, rhinitis, gastrointestinal allergy, food allergy, and asthma. However, published statements and scientific opinions disagree about the clinical usefulness.ObjectiveA World Allergy Organization Special Committee on Food Allergy and Nutrition review of the evidence regarding the use of probiotics for the prevention and treatment of allergy.MethodsA qualitative and narrative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
91
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 168 publications
(187 reference statements)
1
91
0
8
Order By: Relevance
“…In most studies, single or several strains of lactobacilli and bifidobacteria have been used for treatment and prevention of allergic disease; the demonstrated effect of one probiotic strain cannot be extrapolated to another strain. Some probiotics exert immunomodulatory effects, mostly shown in experimental models but also in human intervention studies 8,70 . Mechanistic effects are thought to be mediated by Toll-like-receptors (TLR) to promote Th-1 cell differentiation, through enhanced production of IL-10, TGF-ß and IgA, inhibition of antigen-induced T-cell activation and suppression of TNF 8,70 .…”
Section: Probioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…In most studies, single or several strains of lactobacilli and bifidobacteria have been used for treatment and prevention of allergic disease; the demonstrated effect of one probiotic strain cannot be extrapolated to another strain. Some probiotics exert immunomodulatory effects, mostly shown in experimental models but also in human intervention studies 8,70 . Mechanistic effects are thought to be mediated by Toll-like-receptors (TLR) to promote Th-1 cell differentiation, through enhanced production of IL-10, TGF-ß and IgA, inhibition of antigen-induced T-cell activation and suppression of TNF 8,70 .…”
Section: Probioticsmentioning
confidence: 99%
“…Some probiotics exert immunomodulatory effects, mostly shown in experimental models but also in human intervention studies 8,70 . Mechanistic effects are thought to be mediated by Toll-like-receptors (TLR) to promote Th-1 cell differentiation, through enhanced production of IL-10, TGF-ß and IgA, inhibition of antigen-induced T-cell activation and suppression of TNF 8,70 . The timing of probiotics for promoting immune tolerance appears critical 8 , and a combination of pre and postnatal probiotic supplementation for allergy prevention (namely eczema) has shown the most consistent benefit, although their routine use cannot be recommended 8,30,70 .…”
Section: Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent World Allergy Organization systematic review 6 concurred with an earlier Cochrane Database review 7 in stating that there is not yet an established role for probiotics in preventing or treating allergies. However, the groups emphasized a need for more basic microbial research, such as that presented by Kozakova et al Evidence for protection against allergic airways disease has been shown in rodent models.…”
mentioning
confidence: 93%